Evaluation of Radio over Plastic Optical Fiber Communications - Waseem, Muhammad; Lopez Lucia, Alicia; Carro Ceballos, Pedro Luis; Losada Binué, María Ángeles (Jornada de Jóvenes Investigadores del I3A, 2022)
In this work, we have experimentally evaluated the performance of a Radio over Plastic Optical Fiber (RoPOF) communications link by simultaneously transmitting Long-Term Evolution (LTE) and Narrow-Band Internet of Things (NB-IoT) signals over 75-meters of PMMA large-core Graded-Index POF (GI-POF).